2021
DOI: 10.1111/pbi.13723
|View full text |Cite
|
Sign up to set email alerts
|

Strong and tunable anti‐CRISPR/Cas activities in plants

Abstract: CRISPR/Cas has revolutionized genome engineering in plants. However, the use of anti-CRISPR proteins as tools to prevent CRISPR/Cas-mediated gene editing and gene activation in plants has not been explored yet. This study describes the characterization of two anti-CRISPR proteins, AcrIIA4 and AcrVA1, in Nicotiana benthamiana. Our results demonstrate that AcrIIA4 prevents site-directed mutagenesis in leaves when transiently co-expressed with CRISPR/Cas9. In a similar way, AcrVA1 is able to prevent CRISPR/Cas12a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…Recently, it was reported that a split prime editor system could mediate endogenous base transversion and insertion in human cells . And it has been shown that Tobacco etch virus (TEV)-based system and Potato virus X (PVX)-based vector can infect N. benthamiana simultaneously . Therefore, the identification of multiple valid split sites provides more choice for split SpCas9 and can be potentially used for the delivery of CRISPR/Cas9-based tools such as base editor, prime editor, and CRISPR interference/activation through viruses/nanoparticles-mediated transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that a split prime editor system could mediate endogenous base transversion and insertion in human cells . And it has been shown that Tobacco etch virus (TEV)-based system and Potato virus X (PVX)-based vector can infect N. benthamiana simultaneously . Therefore, the identification of multiple valid split sites provides more choice for split SpCas9 and can be potentially used for the delivery of CRISPR/Cas9-based tools such as base editor, prime editor, and CRISPR interference/activation through viruses/nanoparticles-mediated transformation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, small molecules can be used to deactivate Acr proteins and induce genome editing. Calvache et al fused AcrIIA4 to minimal auxin-inducible degron (mAID), such that the fusion protein can be degraded by auxin treatment through the ubiquitin-proteasome pathway ( Figure 6 C) [ 100 ]. Indeed, treatment with auxin (indole-3-acetic acid) degraded the Acr fusion proteins and induced dCas9-based gene activation in plant cells.…”
Section: Small-molecule Control Of Anti-crispr Proteinsmentioning
confidence: 99%
“…NHEJ is the active DNA repair mechanism in nature wherein Cas9-induced DSBs are repaired ( Moore and Haber 1996 ). NHEJ can, therefore, lead to small insertions or deletions that could yield a host of mutations ( Calvache et al, 2022 ; Wada et al, 2022 ). Such mutations are beneficial while knocking out a targeted gene using CRISPR/Cas9 systems.…”
Section: Repurposing Native Clustered Regularly Interspaced Short Pal...mentioning
confidence: 99%
“…To this effect, HDR is a more obvious choice of DSB repair mechanism for incorporation of desired sequences following cleavage by Cas9. In plants, GE HDR relies on a DNA template along with the gDNA and Cas9 for a successful DSB repair ( Calvache et al, 2022 ; Wada et al, 2022 ). In plants, through genetic engineering, many outstanding repairs have been achieved via HDR, leading to gene replacement, DNA correction, and targeted knockouts.…”
Section: Repurposing Native Clustered Regularly Interspaced Short Pal...mentioning
confidence: 99%